2014
DOI: 10.1111/soin.12064
|View full text |Cite
|
Sign up to set email alerts
|

Learning to “Deal” and “De‐escalate”: How Men in Nursing Manage Self and Patient Emotions

Abstract: While prior research has explored how gender frames emotion management processes, little work has specifically examined the links between men's emotion management in a caring profession and theory on masculine emotionality. Stereotyped as less sensitive to their own and others' emotions, male nurses confront unique challenges in navigating the profession's emotional demands. Drawing on men's diaries and interviews, I examine emergent emotion-based processes that characterize men's emotional labor-the strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 70 publications
(74 reference statements)
3
33
0
2
Order By: Relevance
“…Mason goes on to describe how men's touch can be potentially viewed as sexual and, as a result, men must express their care within the Bstrict parameters^of how others will interpret their actions. This limitation in comforting patients suggests that male nurses' emotion management strategies (Cottingham 2015) might be reframed as alternative ways of mobilizing emotional capital.…”
Section: Emotional Capital and Practice: Capacity Vs Expressionmentioning
confidence: 99%
“…Mason goes on to describe how men's touch can be potentially viewed as sexual and, as a result, men must express their care within the Bstrict parameters^of how others will interpret their actions. This limitation in comforting patients suggests that male nurses' emotion management strategies (Cottingham 2015) might be reframed as alternative ways of mobilizing emotional capital.…”
Section: Emotional Capital and Practice: Capacity Vs Expressionmentioning
confidence: 99%
“…In past work, I have looked at men's emotional labor in nursing (Cottingham, 2015;Cottingham, Johnson, & Taylor, 2016), as well as how their narratives help us better conceptualize emotional capital (Cottingham, 2016). Turning to their narratives here, my aim is to understand how experiences-as situational encounters with evolving practical demands-can feed back into men's conception of masculinity.…”
Section: Case Study Of Men In Nursingmentioning
confidence: 99%
“…Men emulating a managerial caregiving style typically compartmentalize their family caregiver identity and do not allow it to permeate other roles, thereby reducing caregiving burden (Thompson, 2002). Given that professional caregiving men also use this approach (Cottingham, 2015), it is plausible that this caregiving style is more prevalent among double- and triple-duty caregiving men. Indeed, the Anjos et al (2012) study found that men typically assumed a managerial position within their familial care network.…”
Section: Introductionmentioning
confidence: 99%